Bank Deposit Rate Clustering: Theory and Empirical Evidence - Kahn, Charles; Pennacchi, George; Sopranzetti, Ben (Journal of Finance, 1999)
Like security prices, retail deposit interest rates cluster around integers and “even” fractions. However, explanations for security price clustering are incompatible with deposit rate clustering. A theory based on the limited recall of retail depositors is proposed. It predicts that banks tend to set rates at integers and that rates are “sticky” at these levels. The propensity for integer rates increases with the level of wholesale interest rates and deposit market concentration. When banks set noninteger rates, rates are more likely to be just above, rather than just below, integers. The paper finds substantial empirical support for the theory's implications.